PERTANGGUNGJAWABAN PERDATA TERHADAP PEMBERI DANA DONASI MASYARAKAT SECARA ONLINE - Kartika Sari; Firdaus Firdaus; Setia Putra (Lafadz Jaya Publisher, 2023)
Fundraising in Indonesia is a philanthropic activity that requires legal and sociological attention. The fundraising activity is a reflection that humans have an ethic of care for each other. In Indonesia, the implementation of the fundraising is regulated in Law Number 6 of 1961 concerning the Collection of Money and Goods. This law is the basic guideline for every platform that organizes donations, including a foundation. Along with the times, technology and digitalization have become the latest trends that are in demand by the wider community. The fundraising practice studied in this study is a crowdfunding donation system that has the potential to cause legal problems. As for the legal issue, it is about how to take civil legal responsibility for the misuse of donated funds by the Foundation/organizing platform. On the other hand, this study also wants to describe how the technical procedures for a legal entity in the form of a foundation or its derivatives are in raising funds. This study also wants to see who are legal subjects who can become fundraisers in Indonesia. Therefore, there needs to be a civil legal approach in responding to such unlawful acts. This research is a normative legal research. This is based on library research that takes quotes from reading books, or supporting books that have something to do with the problem to be studied. Add data sources Primary, secondary and tertiary data sources are the characteristics of this research. This study also uses qualitative data analysis and produces descriptive data. From the results of the research and discussion carried out, there are several conclusions obtained, namely:First, the regulation regarding donation based fundraising (crowdfunding donation system) does not yet have a clear arrangement regarding the subject who can do the fundraising, whether it is mandatory in the form of a business entity or not. This can be seen through the presence of various kinds of related laws and regulations, that there is no specific explanation regarding the procedures for raising these funds. Fundraising is mostly interpreted as a mere volunteer policy, so there needs to be normativity that regulates this fundraising. Second, fundraising through this donation system (crowdfunding system donation) is also inseparable from legal consequences when the allocation of funds is not in accordance with the mandate of the existing law. Supposedly, legal subjects suspected of misusing donated funds can be held civilly responsible through compensation or other compensation to existing donors.